Analisis Pemilihan Moda Angkutan Komoditi Ayam Petelur di Kabupaten Sidenreng Rappang – Sulawesi Selatan - Asri Amir; Hakzah Hakzah; Abd Muis (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
Sidenreng Rappang Regency - South Sulawesi is one of the largest contributors of laying chicken commodities and is distributed to various regions. This research aims to determine the characteristics and choice of transportation modes. This research uses a descriptive quantitative method based on surveys and interviews with 170 respondents using AHP analysis. The results of the research show that the characteristics of the transportation used are pick-up trucks (2 tons), single-wheel trucks (5 tons), 2-axle trucks (8 tons). The dominant departure time during the day is 12.00-14.00 WITA, at night 22.00-00.00 WITA, while the arrival time at the distribution point during the day is predominantly 14.00-16.00 WITA, and at night 00.00-02.00 WITA. The dominant spread is to Makassar City, while outside the province, namely West Sulawesi Province. The choice of efficient transportation mode used in the process of distributing laying hens is the Pick Up mode with a priority weight percentage of 0.61%.